(untitled) (Studia Archaeologica, 2022)
The Institute of Archaeology, MAS has a rich collection of archaeological artifacts discovered by generations of archaeologists since the 1940s. The Institute has been planning and implementing the works to improve the preservation and protection of the collection, restoration of artifacts, and training specialists in stages. Since 2012, comprising 1904 items of archaeological artifacts were restored in the laboratory of Institute, those are 591 items metal objects, 45 items ceramic potteries from the Eneolithic period to the Mongolian empire, 1120 items of Buddha statues of Tathagatas, 64 items of religious objects, and 84 items of wood, bone, and leather found from cave burials. In this article the authors presented the results of the conservation, preservation, and restoration of artifacts, achievements, problems faced, and how they were solved. Археологийн олдворын сэргээн засварлалтын зарим асуудлаас Товчлол. ШУА-ийн Археологийн хүрээлэн нь 1940-өөд оноос хойш үе үеийн археологичдын судалж илрүүлсэн олдворын арвин баялаг сан хөмрөгтэй билээ. Археологийн хайгуул, малтлага судалгааны ажлын үр дүнд цуглуулсан олдвор хэрэглэгдэхүүний хадгалалт хамгаалалт, сэргээн засварлах ажлын үр дүн, ололт амжилт, тулгарч байсан асуудал бэрхшээл, түүнийг хэрхэн шийдвэрлэсэн талаарх үр дүнг тоймлон өгүүлэхийг зорив. Түлхүүр үгс: Археологийн олдвор, сэргээн засварлалт, хадгалалт хамгаалалт